2001
DOI: 10.1136/bjo.85.7.782
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus in pterygium

Abstract: Aim-To determine the prevalence and significance of human papillomaviral types in conjunctival pterygia. Methods-Polymerase chain reaction technology was used to identify the presence of human papillomavirus (HPV) in 10 formalin fixed paraYn embedded pterygia samples. 10 conjunctival papillomas were used as positive controls. 20 conjunctival samples, 10 with primary acquired melanosis and 10 with malignant melanoma, were used as negative controls. Sample subgroups were of equal sex, race, and age distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1
10

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 10 publications
2
76
1
10
Order By: Relevance
“…The most frequent diagnoses were cataract (37%), chalazia (12%), corneal tears (10%), and eye trauma (9%). Patients presenting with pterygium or pingueculum were not included because it was previously suspected that these diseases were associated with HPV infection (Gallagher et al, 2001). A total of 309 controls were included.…”
Section: Study Participantsmentioning
confidence: 99%
“…The most frequent diagnoses were cataract (37%), chalazia (12%), corneal tears (10%), and eye trauma (9%). Patients presenting with pterygium or pingueculum were not included because it was previously suspected that these diseases were associated with HPV infection (Gallagher et al, 2001). A total of 309 controls were included.…”
Section: Study Participantsmentioning
confidence: 99%
“…Recently, Sjö et al 9 reported that PCR gave positive results for HPV in 86 (81%) of 106 papilloma specimens studied. In addition, HPV was detected in all five papilloma cases studied by Saegusa et al, 19 and in 9 of 10 papilloma cases (90%) studied by Gallagher et al 3 The presence of HPV in papilloma has also been confirmed by Southern blotting and in situ hybridization. 20 Based on these reports and our data, it is likely that HPV is closely involved in the pathogenesis of conjunctival papillomas.…”
Section: Discussionmentioning
confidence: 63%
“…8,9 Also, several studies have shown that HPV DNA can be detected in pterygium by PCR. 3,10,11 However, the proportion of cases that are positive for HPV DNA shows marked variation; HPV DNA has been detected in up to 50% cases of pterygium, whereas other studies have failed to detect any. 12 Therefore, the involvement of HPV in the pathogenesis of pterygium remains controversial.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, pterygia display some tumourlike properties in their clinical appearance of local invasion and epithelial cell metaplasia. 2 Furthermore, the presence of oncogenic viruses, such as the human papilloma virus and herpes simplex virus, 3,4 loss of heterozygosity, 5 and abnormal p53 expression in pterygium lesions, 6,7 all suggest the possible neoplastic nature of pterygium. A model of pterygium formation is then proposed, in which genetic predisposition, environmental factors, and viral infections may participate in the multistep process.…”
Section: Introductionmentioning
confidence: 99%